Optical properties of GaSe semiconducting crystals intercalated by CdTe nanoparticles - Khalavk, Y.B.; Shcherbak, L.P.; Pyrlya, M.M.; Boledzyuk, V.B.; Kovalyuk, Z.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
The transmission spectra of GaSe crystals intercalated by CdTe nanoparticles
(NPs) from aqueous colloidal solutions were investigated at 77 K in the range of GaSe
excitonic absorption. Solutions of two types – yellow (with 1-2.5 nm NPs) and orange
(with 2.5-3.5 nm NPs) – were used for the experiments. Essential GaSe optical density
intensity growth in proportion to exposition time was observed after intercalation from
yellow solutions up to 50 days. While the exciton peak position (near 2.1 eV) coincides
both in “pure” GaSe and GaSe(CdTe) after intercalation from yellow solution, the
shortwave shift is observed for GaSe(CdTe) intercalated from the orange solutions. The
results are discussed in assumption of strain effect presence.